Extending operational range - Henkensmeier, Dirk (NATURE PUBLISHING GROUP, 2022)
Fuel cells with acid-doped membranes must avoid liquid water and humid gas streams to prevent leaching of acid, and so are limited to operating above 120 degrees C, complicating start-up. Now, microporous membranes offer a chance to confine the acid to their pores, allowing start-up without pre-heating, higher performance and perhaps even extended lifetime.